Effects of a human rights education intervention with Social Work students: assessment of concepts and commitment - Cubillos-Vega, Carla; Ferrán-Aranaz, Magdalena (Cuadernos de Trabajo Social, 2019)
Two of the current challenges for human rights education (HRE) are the development of tools to evaluate it and the dissemination of experiences to improve it. This work outlines the findings of an HRE intervention with university students. The research had a quasi-experimental design with a control group, applying pre-test and post-test measures via the use of two validated instruments. The findings point to significant differences between the control group and the intervention group. The significant increase in concepts of and commitment to human rights in the intervention group provides evidence to support the argument that there is a positive association between knowledge of and commitment to human rights.